Peningkatan Kompetensi Literasi Digital Guru Melalui Bimtek Pembuatan Media dan Evaluasi Pembelajaran - Anisah, Anisah; Darmansyah, Darmansyah; Irsyad, Irsyad (Abdi: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Online learning (on the network) is a demand in the 4.0 era (current industrial revolution. This is because of the development of technology and information so that learning must be carried out using technology. In addition, the Covid-19 outbreak gave birth to implementation policies learning carried out at home using online methods. For this reason, teachers are required tohave today’s digital literacy competencies in order to be able to do online learning. However, the current problem is that there are still many teachers who do not understand technology digital, namely 97.5% of teachers. This is as known from the results of interviews in Malalak District Agam Regency, West Sumatra that there are still many teachers who have not been able to implement learning using digital technology. And also there are still many teachers who are not able to carry out online learning. There are still many teachers who have not been able to evaluate online learning. The solution to overcome these problems is to transfer knowledge through online learning guidance for teachers. The first step is to do testing digital literacy competence of teachers through a questionnaire. After that give understanding to the teacher about online learning. Then the next stage is conducting technical guidance on the manufacture of innovative and interactive learning media for learning. Next, technical guidance is carried out about the implementation of online learning evaluation for teachers. The last stage is to evaluate about the digital literacy competence of teachers regarding the implementation and evaluation of online learning using a questionnaire. The output of the results of this community service activity are scientific publications, namely: articles on Journals with ISSN / Proceedings of National journals, namely colloquium journals, video service activities, and publication in print/online mass media, namely the Haluan newspaper. And also activity report.